1998
DOI: 10.1161/01.cir.97.25.2567
|View full text |Cite
|
Sign up to set email alerts
|

Postrepolarization Refractoriness Versus Conduction Slowing Caused by Class I Antiarrhythmic Drugs

Abstract: Background-Conduction block may be both antiarrhythmic and proarrhythmic. Drug-induced postrepolarization refractoriness (PRR) may prevent premature excitation and tachyarrhythmia induction. The effects of propafenone and procainamide on these parameters, and their antiarrhythmic or proarrhythmic consequences, were investigated. Methods and Results-In 11 isolated Langendorff-perfused rabbit hearts, monophasic action potentials (MAPs) were recorded simultaneously from six to seven different right and left ventr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
62
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(67 citation statements)
references
References 55 publications
4
62
1
Order By: Relevance
“…More importantly, the prolongation of the MAP duration was more marked than that of the ERP in the chronic phase, particularly at a slower heart rate, indicating the prolongation of the electrically vulnerable period of the ventricle. These local electrophysiological changes indicate increase in the risk of aberrant excitation, which may provide a "substrate" for re-entry arrhythmias, leading to the onset of TdP (14,15).…”
Section: Local Proarrhythmic Substratesmentioning
confidence: 99%
“…More importantly, the prolongation of the MAP duration was more marked than that of the ERP in the chronic phase, particularly at a slower heart rate, indicating the prolongation of the electrically vulnerable period of the ventricle. These local electrophysiological changes indicate increase in the risk of aberrant excitation, which may provide a "substrate" for re-entry arrhythmias, leading to the onset of TdP (14,15).…”
Section: Local Proarrhythmic Substratesmentioning
confidence: 99%
“…Moreover, a MAP recording/pacing combination catheter was used to Circulation Journal Vol.66, September 2002 simultaneously measure both MAP and effective refractory period (ERP) at the same site to assess the drug effects on the terminal repolarization period (phase 3) of the action potential. [3][4][5][6][7][8][9][10][11][14][15][16][17] …”
mentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10][11] Class I drugs are known to affect the QT interval, 12,13 but information regarding the effects of class I antiarrhythmic drugs in this type of model is still limited. [14][15][16][17] In this study, we simultaneously assessed the in vivo electrophysiological and cardiohemodynamic effects of typical class I antiarrhythmic drugs, disopyramide and mexiletine, using the halothane-anesthetized canine model. To better analyze the electrophysiological effects on the depolarization/repolarization process, we recorded His bundle electrograms and monophasic action potentials (MAPs), respectively, in addition to the standard lead II surface ECG.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, in the present study, seeking a more quantitative methodological approach, we related SS to arrhythmia inducibility. By using a similar approach, Kirchhof et al (1998Kirchhof et al ( , 2003 showed the antiarrhythmic and proarrhythmic effects on ventricular fibrillation of amiodarone, procainamide and propafenone. Therefore, the use of SS seems to be suitable for the evaluation of arrhythmia inducibility in diverse experimental conditions.…”
Section: Discussionmentioning
confidence: 99%